Iowa RBA, June 8, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Notes for the Iowa RBA for June 8, 1998. Highlights include Black-headed Gull, Eurasian Collared Dove and some late migratory birds. Includes notes for updates for June 10 and June 11. Epson - sheet feed/flatbed